2021
DOI: 10.1002/nop2.762
|View full text |Cite
|
Sign up to set email alerts
|

Work environment for hospital nurses in Japan: The relationships between nurses' perceptions of their work environment and nursing outcomes

Abstract: Aim: To investigate nurses' perceptions of their work environment and to investigate the relationships between variables measuring the work environment (WE) and nursing outcomes (NOs).Design: A 2-year prospective longitudinal survey (2013)(2014)(2015). Method(s):Descriptive statistics of nurse demographics, organizational WE and NOs were calculated by position. The associations between Practice Environment Scale of the Nursing Work Index (PES-NWI) and NOs were examined for each unit. Results:The participants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 27 publications
1
30
0
Order By: Relevance
“…Consistent with our findings, Cho and Han (2018) found that a healthy work environment would improve job performance among nurses (Cho & Han, 2018). Moreover, Ogata et al (2021) revealed that the work environment directly improves employee performance, and this was also confirmed by Ambani et al (2020).…”
supporting
confidence: 85%
See 2 more Smart Citations
“…Consistent with our findings, Cho and Han (2018) found that a healthy work environment would improve job performance among nurses (Cho & Han, 2018). Moreover, Ogata et al (2021) revealed that the work environment directly improves employee performance, and this was also confirmed by Ambani et al (2020).…”
supporting
confidence: 85%
“…Recent evidence has revealed that work environments play a significant role in nurses' ability to provide quality care. According to (Ogata et al, 2021), the higher the positive work environment, the better the nursing outcomes, confirming a significant relationship between work environment and nurse outcomes, such as job satisfaction, retention or resignation and health status. However, most nurses working in public hospitals in Saudi Arabia are recruited from different countries, including Arab countries, India, the Philippines, and Pakistan.…”
Section: Nursing Practice Environmentmentioning
confidence: 88%
See 1 more Smart Citation
“…The impact of the work environment on job performance (Sarıköse & Göktepe, 2022;Cho & Han, 2018;Wafa'a, Alhurani, Alhalal, Al-Dwaikat, & Al-Faouri, 2020;Ogata, et al, 2021;Edem, Akpan, & Pepple, 2017;Mohamed & Gaballah, 2018;Bhatti, Mat, & Juhari, 2018;Shahnavazi, Eshkiki, Shahnavazi, & Bouraghi, 2021;Sadewo, Surachman, & Rofiaty, 2021)…”
Section: )mentioning
confidence: 99%
“…Work environments involve essential factors that organisations must consider when seeking to understand the performance of employees at work. This research study intends to review the current literature on the research concepts 'work environment' and 'job performance', which are crucial for an organisation's growth (Ogata et al, 2021). In addition, understanding the effect of the work environment on nurses' job performance could lead to many benefits for leaders, nurses and health organisations.…”
Section: Introductionmentioning
confidence: 99%